Investigating Modern Art. - Barber, Fionna; Batchelor, David; Bland, Josie; Dawtrey, Liz; Gisbourne, Mark; Harris, Jonathan; Jackson, Toby; Masterton, Mary; Meecham, Pam; Overy, Paul; Sheldon, Julie; Wood, Paul (The Arts Council of England The Open University, 1996)
Modern art sometimes appears to be difficult, or even incomprehensible, and as a result has been subject to scepticism and ridicule. This book provides an accessible historical progression through the modern period, focusing on particular artists and works of art, while attempting to draw out more general issues and implications. The discussion of key figures such as Picasso, Matisse, Pollock and Warhol, and movements such as Cubism, Surrealism, Abstract Expressionisme and Minimal Art is animated by the most relevant concerns of contemporary art historical scholarship. Issues of gender and ethnicity, criticisms of the accepted canon of modern art, and important social and poliitcal influences upon the institutions of art are interwoven with the discussion of particular works. Since the end of the last century Modernism has been the dominant force in the production of western avant-garde art. Recently many of the values assumed by the modernist avant-garde have come under fundamental scrutiny. This collection of essays aims to equip its readers with the tools to understand these debates. Modernist myths which have appeared to make art elitist or inaccessible, or simply irrelevant, are examined as is Postmodernism, when the questions of whether we in the late twentieth century are witness to the end of the modern period, and whether the diversity of contemporary art mirrors this situation are debated. This book will provide a simulating and informative basis for critical discussion of modern artists, art movements and art works from a variety of viewpoints. Readers will find points to disagree with, and much to generate further debate and enquiry.
Andre, Carl ; Beuys, Joseph ; Biswas, Sutapa ; Braque, Georges ; Brodsky, Isaac ; Burgin, Victor ; Caro, Anthony ; Carrington, Leonora ; Chicago, Judy ; Dali, Salvador ; Duchamp, Marcel ; Ernst, Max ; Riverhead (New York) ; Gauguin, Paul ; van Gogh, Vincent ; Golub, Leon ; González, Julio ; Grosz, George ; Haacke, Hans ; Hart Benton, Thomas ; Heartfield, John ; Höch, Hannah ; Hopper, Edward ; Johns, Jasper ; Jorn, Asger ; Judd, Donald ; Kandinsky, Wassily ; Killip, Chris ; Kirchner, Ernst Ludwig ; Kollwitz, Kathe ; Koons, Jeff ; Kruger, Barbara ; Lamba, Jacqueline ; Le Corbusier ; LeWitt, Sol ; Lichtenstein, Roy ; Magritte, René ; Man Ray ; Masson, Andre ; Matisse, Henri ; Messager, Annette ; Miro, Joan ; Mondriaan, Piet ; Noland, Kenneth ; Nolde, Emil ; Orozco, José ; Paik, Nam June ; Picabia, Francis ; Picasso, Pablo ; Pollock, Jackson ; Rauschenberg, Robert ; Rietveld, Gerrit ; Rothko, Mark ; Sherman, Cindy ; Smith, David ; Tanguy, Yves ; Tatlin, Vladimir ; Warhol, Andy
Engels
boek